Dramáticas do uso do corpo-si: uma análise do trabalho do enfermeiro em terapia intensiva - Pinno, Camila (2020)
Intensive care work is characterized by its dynamism and the continuous experience of dramatic use of the body-self by the nurse. In this sense, the objective was to analyze how the dramatic use of the body-self occurs by nurses in intensive care. Qualitative research, of the multiple case study type. One of the cases was developed with intensive care nurses from a public hospital and the other with intensive care nurses from a private hospital. Data were collected from March 2018 to March 2019; aiming at the triangulation of sources of evidence, based on documentary research, interview and systematic observation. Data were assessed through thematic content analysis and from the perspective of the theoretical framework of ergology. 14 nurses participated in the study, being nine workers from the public ICU and five from the private ICU. Initially, a description of the research scenarios - nurses' work environment: characterization of adult intensive care units was carried out. The other results were organized into the following thematic categories: 'dramatic use of the body-self: the real work of the nurse in intensive care' and 'factors that can facilitate or hinder the dramatic use of the body-self by the nurse in intensive care'. Finally, there was a ‘cross-synthesis of cases: an analysis of the dramatic use of the body-self by nurses in intensive care’. From the results of the first category, it became evident that the factors that can influence the dramatic use of the body itself, by the nurse, are the subjectivity and personal values of the nurse, institutional norms, knowledge and professional experience. The real work of nurses in UTIA is permeated by the prescribed work, by the organization of work when establishing priorities, by work with and under the influence of the multiprofessional team, by the occurrence of renormalizations of activities, both in carrying out administrative and assistance nursing activities. In the second thematic category, it was evidenced that the nurses of the two ICUs corroborated about the factors that can facilitate the dramatic use of the body-self, namely: work experience, knowledge, support from the head of nursing, professional autonomy, nursing prescription, use of prescribed work, good comunication between the multidisciplinary team. As for the factors that can hinder the dramatic use of the body-self by nurses, the “style” of work / subjectivity of each medical professional stood out, the lack of support from the institution to participate in events, the lack of knowledge in specific work activities ; the lack of material and human resources. The results also point out that the clinical characteristics and the needs that the patients had, had a direct influence on the dramatic use of the body-self, by the nurse. Regarding the personal characteristics of the research participants, it can be inferred that the ICU nurse who has a longer experience in his profession may be more likely to perform some work activity. Finally, the thesis on which this investigation is based is that: nurses, when working in UTIA, experience dramatic use of the body-self that involve aspects based on their subjectivity, their values, their knowledge and experience of work and the way work is prescribed in health institutions. It is concluded that the thesis was confirmed, as the data indicated that the nurse experiences dramatic use of the body itself, in intensive care work, influenced by several factors.